LABOR ABSORPTION AND ECONOMIC GROWTH IN THE PERSPECTIVE OF ISLAMIC ECONOMICS: AN EMPIRICAL ANALYSIS - Eny Widiaty; Nur Fazillah Milawati; Sahirul Alim (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2026)
Economic growth is a key indicator of development performance, yet its relationship with labor absorption remains a critical issue, particularly when assessed from the perspective of Islamic economics. This study aims to examine the effect of labor absorption on economic growth within the framework of Islamic economic principles, emphasizing justice (al-‘adl), welfare, and social responsibility. The research employs a quantitative empirical approach using secondary data obtained from official statistical sources and institutional reports over a multi-year period. Data analysis is conducted using simple linear regression to identify the direction and significance of the relationship between labor absorption and economic growth. The results indicate that labor absorption has a negative effect on economic growth, suggesting that increases in employment are not necessarily accompanied by improvements in productivity or equitable income distribution. From the perspective of Islamic economics, these findings highlight the importance of aligning employment expansion with productivity enhancement, distributive justice, and social welfare to achieve sustainable and inclusive economic growth. This study contributes to empirical discussions on labor and growth by integrating Islamic economic values into the analysis and offers insights for policymakers in designing development strategies that are both economically effective and ethically grounded.